Kinetics of Lifetime Changes in Bimetallic Nanocatalysts Revealed by Quick X‐ray Absorption Spectroscopy - Filez, Matthias; Poelman, Hilde; Redekop, Evgeniy A.; Galvita, Vladimir V.; Alexopoulos, Konstantinos; Meledina, Maria; Ramachandran, Ranjith K.; Dendooven, Jolien; Detavernier, Christophe; Van Tendeloo, Gustaaf; Safonova, Olga V.; Nachtegaal, Maarten; et al. (Angewandte Chemie International Edition, 2018)
Alloyed metal nanocatalysts are of environmental and economic importance in a plethora of chemical technologies. During the catalyst lifetime, supported alloy nanoparticles undergo dynamic changes which are well‐recognized but still poorly understood. High‐temperature O2–H2 redox cycling was applied to mimic the lifetime changes in model Pt13In9 nanocatalysts, while monitoring the induced changes by in situ quick X‐ray absorption spectroscopy with one‐second resolution. The different reaction steps involved in repeated Pt13In9 segregation‐alloying are identified and kinetically characterized at the single‐cycle level. Over longer time scales, sintering phenomena are substantiated and the intraparticle structure is revealed throughout the catalyst lifetime. The in situ time‐resolved observation of the dynamic habits of alloyed nanoparticles and their kinetic description can impact catalysis and other fields involving (bi)metallic nanoalloys. Kinetics captured: The steps involved in repetitive Pt‐In catalyst alloying and segregation are kinetically identified during H2–O2 redox cycling by in situ quick X‐ray absorption spectroscopy (QXAS). Rate laws, coefficients, and activation energies are extracted from QXAS, which allows the construction of the kinetic reaction pathways that steer the dynamic restructuring of alloyed nanocatalysts during their lifetime.